Fibrilación ventricular: la arritmia más desafiante. Parte I. Ventricular fibrillation: the more defiant arrhythmia. Part I - Margarita Dorantes Sánchez; Amarily López Delgado (ECIMED, 2011)
Ventricular fibrillation (FV) it is one of the most defiant rhythm disorders and the most seriousone, the oldest described arrhythmia, the one that it's less known, the most complex,the not resolved: "ventricular fibrillation... is a beast". Ventricular fibrillation is a complex anddynamic phenomenon of electric disorder. In fact it is a family of arrhythmias, an uniquemodel doesn't exist although more typical patterns might be found. They are electrocardiographicand electrophysiological differences; also in their phisiopatologycal mechanisms, beginningways and perpetuation, triggers and therapeutic necessities. There is chaos and organizationin it, from a bigger disorder it can pass to a smaller one with time-space periodicity,repeatability, regularity and vice versa; that is to say, from incoherence to coherence orin inverse way.The fibrillation result when an electric wave front induces reentrance and it unchains a cascadeof new fronts of waves. The increment in tisular heterogeneity caused by the electric orstructural remodeling associated to the illness process, has been traditionally involved with abigger inclination to wave front→ reentrance→ fibrillation in sick hearts.The future of the ventricular fibrillation will be: to prevent it, to identify the prone subjects tosuffer it, to deepen in the knowledge of the genetic-acquired causes, to achieve that their organizationdegree increases by means of antiarrthymic drugs, to make it not sustained, totransform it in a longer life reentrance, to understand the individual differences and to modifythe answers of channel-membrane-receptors-pumps.